Empleabilidad y rentabilidad de las carreras universitarias de la región centro del Perú: desafíos para la gestión universitaria peruana - Espinoza Avellaneda, Yime (2021)
The article shows the probability of employability and profitability of graduates from universities in the Junín region in 2018, dispersed in adjoining departments (Huancavelica, Cerro de Pasco, Huánuco and Ayacucho), with information obtained through personal interviews and employment information from ENAHO-2018, gaps in employability and profitability were identified, by type of academic training, gender and university regimes. It was identified that a university professional achieves full employability and maximum profitability around 40 and 43 years respectively and among the factors that determine they are related to university education, the regime and type of university career, age, sex and marital status.